Differential regional and cellular distribution of β-amyloid precursor protein messenger RNAs containing and lacking the kunitz protease inhibitor domain in the brain of human, rat and mouse - Sola`, C.; Mengod, G.; Probst, A.; Palacios, J.M. (Neuroscience, 1993)
The β-amyloid precursor protein is the precursor of the main component of senile plaques (the β-amyloid peptide or β/A4) found in the brain of aged humans and, in higher amounts, in the brain of Alzheimer's disease and Down's syndrome subjects. Four different forms of β-amyloid precursor protein messenger RNAs have been described in humans and rodents: β-amyloid precursor protein 695, β-amyloid precursor protein 714, β-amyloid precursor protein 751 and β-amyloid precursor protein 770 messenger RNAs (numbers corresponding to the number of encoded amino acids). The two latter forms are characterized by containing in their sequence a region with high homology to the Kunitz family of serine protease inhibitors. We have used oligonucleotide probes to study the distribution of the different messenger RNAs encoding each of the four β-amyloid precursor proteins by in situ hybridization histochemistry in human, rat and mouse brain. We found that β-amyloid precursor protein 695, β-amyloid precursor protein 714 and β-amyloid precursor protein 751 messenger RNAs were widely distributed in the human, rat and mouse brain and that their distribution was roughly similar in most brain areas in these three species. The distribution of β-amyloid precursor protein 770 messenger RNA was not so wide and differed among the three species studied, β-amyloid precursor protein 751 and 770 messenger RNAs were the only forms present at significant levels in rodent choroid plexus and meninges, while β-amyloid precursor protein messenger RNA isoforms containing and lacking the Kunitz domain were detected in the human choroid plexus. We also observed that the relative levels of β-amyloid precursor protein 751 and 770 messenger RNAs in the rat cerebral white matter as well as in the mouse and human striatum were higher than those of the β-amyloid precursor protein messenger RNAs lacking the Kunitz domain. While the most abundant β-amyloid precursor protein messenger RNAs in the brain of all three species under study were, in descending order, β-amyloid precursor protein 695 and β-amyloid precursor protein 751 messenger RNAs, the least abundant form was not the same for all species: in human it was β-amyloid precursor protein 714 messenger RNA and in rat and mouse brain it was β-amyloid precursor protein 770 messenger RNA. Our results show differences both inter- and intraspecies of the relative abundance and distribution of four β-amyloid precursor protein messenger RNAs in rat, mouse and human brain. The non-coincidence of the distribution of β-amyloid precursor protein messenger RNA isoforms suggests different physiological functions for the β-amyloid precursor proteins. Interspecies differences should be considered when comparing results from animal and human studies.